PERKEMBANGAN BUDAYA LOKAL DALAM KEMAJUAN BUDAYA NASIONAL - I Nyoman Temon; Ni Wayan Sukerti (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2022)
National culture needs to be grown and preserved positive, civilized and superior regional cultural values so as to strengthen the identity of the nation's/national culture. In order for the process of socio-cultural change to run smoothly, it is hoped that there will be a wise and responsible attitude in making a decision so that it can be used as a new breakthrough as a filter for the resilience of the nation's culture. Indonesian culture is an integration that is highly respected and its distinctive eastern customs which are firmly held by the Indonesian people, are expected to contribute to the interaction of socio-cultural evolution.